English spelling - Carney, Edward (London ; New York : Routledge, 1997)
Speaking and writing. Finding phonemes. Long and short vowel pairs. Marking vowel length. Complications in length marking. Some consonant spellings...
Keywords: English language; Spelling; Orthography; English language -- Orthography and spelling